The Emergent General Surgical Patient: Evaluation Patterns in the Emergency Department: Emergent Surgical Patient Evaluation - Harpole, Bethany; Helmer, Stephen; Quinn, karson; Chang, Howard; Brown, Nicholas (Kansas Journal of Medicine, 2022)
Introduction. Emergency general surgery patients represent a growing segment of general surgical admissions and national healthcare burden. A paucity of literature exists evaluating the work-up of these patients presenting to the Emergency Department (ED), particularly possible evaluation differentials between emergency physicians and physician assistants or advanced practrice registered nurses (PA/APRNs). The purpose of this study was to evaluate differences in ED work-up of general surgical patients between emergency physicians and PA/APRNs. Methods. A retrospective review was conducted of patients presenting to the ED with the chief complaint of abdominal pain. Demographic data, evaluating provider, laboratory and imaging tests, diagnostic data, and disposition were obtained. Results. Patients median age was 53.5 years, with 49% male and 81.6% Caucasian. Emergency physicians saw a majority (61.2%) of patients. Emergency physicians saw older patients (62.0 vs. 45.5 years, p=0.017), and more patients that were anemic (28.3% vs. 14.3%), or with elevated creatinine levels (46.7% vs. 25.7%). There was no significant difference between groups for time in the ED (6.1 ± 2.4 vs. 5.7 ± 2.6 hrs, p=0.519), time to surgical consult (3.4 vs. 3.3 hrs, p=0.298), or time to OR (29.5 vs. 12.0 hrs, p=0.075). Patients seen by emergency physicians had a longer length of hospital stay (4.5 vs. 2 days, p=0.002). Conclusions. Time in the ED and time to surgical consult did not vary between groups although patients first seen by emergency physicians had potentially higher acuity. Decreased hospital length of stay in patients seen by PA/APRNs may reflect disease-specific differences.